Application of Lipase Based Enzymatic Time Temperature Indicator (TTI) as Quality Marker for Frozen Chicken Meat - Jaiswal, Rohit Kumar; Mendiratta, Sanjod Kumar; Talukder, Suman; Soni, Arvind; Chand, Sagar; Saini, Babu Lal (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2020)
Lipase based enzymatic TTI was prepared using tricaprylin as substrate to monitor thermal abuse history of frozen chicken meat during supply chain. TTI showed an irreversible distinct colour change from initial green to intermediate orange to final red during temperature abuse with corresponding decrease in pH of TTI solution from 8.11 to 6.93 and 5.75, respectively. Temperature dynamicity of TTI on kinetic parameters was derived through Arrhenius equation and activation energy (Ea) of TTI was calculated as 50.94 kJ/mol. At different temperature abuse conditions viz. 5 ± 1 °C, 15 ± 1 °C, 25 ± 1 °C, and 35 ± 1 °C, quantitative changes in various parameters of chicken meat were evaluated and correlated with distinct colour response of TTI. The results showed significant correlation of parameters with colour changes in TTI at 35 ± 1 °C, insignificant correlation at 5 ± 1 °C and 15 ± 1 °C and slight correlation at 25 ± 1 °C indicating concurrent change in quality characteristics of frozen chicken meat on exposure to different temperature abuse conditions. Therefore, suggesting single lipase based enzymatic TTI cannot be utilized for quality marking of frozen chicken meat at different temperature abuse conditions.